Household attitudes, perceptions, and purchasing behavior on locally-produced and imported vegetables - Anciano, Teddy Rizza A.
This study determined the attitudes, perceptions, and purchasing behavior of 100 households on a locally-produced and imported vegetables. The households were purposively chosen to include only those residing in communities and subdivisions classified as middle class areas in Quezon City. A survey was administered to determine their favorable and unfavorable attitudes towards purchasing, regulating importation, supporting local farmers and enhancing knowledge on production. Similarly, it was done to determine their positive and negative perceptions on locally-produced and imported vegetables and their purchasing behavior. Results revealed that these middle class respondents were aware if they are buying locally-produced or imported vegetables and they still buy more locally-produced vegetables. They generally have positive attitudes towards the areas mentioned above and they have positive perceptions on locally-produced vegetables based on quality, price, farming and production practices, taste, nutritional value, desired variety and quantity, and handling and storage. However, in aspects of attractiveness and packaging they perceived imported vegetables as more attractive and better packed and sealed. They buy vegetables every other day, twice a week, or once a week. The average amount spent on vegetables is Php 1232.26 per month, which is approximately 300 per week. Despite the increasing participation of supermarkets in vegetable retailing where most imported vegetables are sold, wet market purchases were still prevalent. More so, their decision on what veget6ables to buy and where to buy them was not considerably influenced by its being produced in our own country or imported from other countries.